О ГРАВИТАЦИИ НА ЧЕРНОЙ ДЫРЕ (World Science, 2019)
A comparative analysis of the gravitational forces of interaction of matter with antimatter and matter with matter was carried out. Comparative analysis showed that gravity on a black hole is many orders of magnitude greater than the interaction of matter with matter. Based on the analysis of research results, it was concluded that the black hole is antimatter.